2015
DOI: 10.1177/0961203315591024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical and serological differences among juvenile-, adult-, and late-onset systemic lupus erythematosus in Korean patients

Abstract: Our results indicate that SLE patients present with different clinical and serological manifestations according to age at disease onset. JSLE patients have more severe disease activity and more frequent renal involvement and LSLE patients have milder disease activity, more commonly accompanied by Sjögren's syndrome, at disease onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
2
12

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 39 publications
10
52
2
12
Order By: Relevance
“…Recently, a study showed that ANA was present in 99.8% of 552 patients with SLE from South China; 81.3% of these subjects also displayed anti‐dsDNA antibodies . Interestingly, a study from Korea showed that anti‐dsDNA was found more frequently in juvenile SLE patients under 18 years old and less frequently in SLE patients over 50 years old ( P < 0.05) . However, the differential diagnosis between OLP and LE is difficult because they have similar oral manifestations .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study showed that ANA was present in 99.8% of 552 patients with SLE from South China; 81.3% of these subjects also displayed anti‐dsDNA antibodies . Interestingly, a study from Korea showed that anti‐dsDNA was found more frequently in juvenile SLE patients under 18 years old and less frequently in SLE patients over 50 years old ( P < 0.05) . However, the differential diagnosis between OLP and LE is difficult because they have similar oral manifestations .…”
Section: Discussionmentioning
confidence: 99%
“…Sicca syndrome, 4 pericarditis, and lung involvement are more common as initial manifestations of LO-SLE. Choi et al 5 reported that decreased complement levels are more common in juvenile SLE. Webb et al 6 reported that doublestranded deoxyribonucleic acid antibody results can be heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…This study was prospective case-control study carried out in the period from August 2016 to August 2017 after approval from the research ethical committee of the faculty of Medicine of Tanta University and informed written or verbal consents from parents of included patients on 50 Lupus patients with ages ranged from 10-18 years who were selected from outpatient clinic and inpatient wards of Pediatric Nephrology Unit of Pediatric Department of Tanta University Hospital who fulfilled the revised criteria of American College of Rheumatology (ACR) for diagnosis of SLE [8,9]. They were subdivided into 2 groups, group 1 included 50 known cases of SLE during renal disease activity (Active lupus nephritis) and group 2 included 30 known cases of SLE without activity (inactive SLE).…”
Section: Methodsmentioning
confidence: 99%